(untitled) - Can Tho university (Vietnam, 2006)
The workshop will take place over four days and will cover the statistical analysis of assemblage data (species by samples matrices of abundance, area cover etc) and/or multi-variable environmental data which arise in a wide range of applications in ecology and environmental impact assessments and monitoring of large-scale biodiversity change, to analysing purely physical or chemical variables.
Keywords: Ecology,Sinh thái học